Tuberculose associada à AIDS: situação de região do Nordeste brasileiro Tuberculosis associated with AIDS: the position in a Northeastern region of Brazil - Ligia R. S. Kerr-Pontes; Fabíola A. S. Oliveira; Cristina A. M. Freire (Revista de Saúde Pública, 1997)
OBJETIVO: Investigar os principais aspectos da co-infecção pelo HIV e o Mycobacterium tuberculosis nos pacientes adultos assistidos pelo hospital de referência para doenças infecciosas do Estado do Ceará, Brasil, responsável pela notificação de 89,3% dos casos registrados no Estado, entre 1986-92. METODOLOGIA: Foram coletados dados de prontuários de pacientes maiores de 15 anos, com diagnóstico de AIDS, atendidos em hospital de referência estadual, região Nordeste do Brasil. A análise dos dados seguem o critério do Ministério da Saúde, para definição dessa doença. RESULTADOS: A tuberculose apresentou-se em 30,6% dos pacientes estudados (151/493) e foi diagnosticada até o primeiro ano após o diagnóstico da AIDS em 76,8% dos casos. Observou-se um tendência crescente na proporção de casos de tuberculose entre pacientes com AIDS conforme decresce o nível de escolaridade (<0,001). A forma extrapulmonar apresentou-se em 23,9% dos casos e a forma miliar em 25% destes casos, diferindo significativamente (p<0,001 para as duas proporções) dos casos com tuberculose sem infecção pelo HIV registrados no Estado, em 1992. CONCLUSÃO: O precoce desenvolvimento da tuberculose, a elevada presença de formas extrapulmonares e a alta letalidade indicam que as medidas de prevenção e controle da AIDS e da tuberculose não devem ser vistas separadamente. INTRODUCTION: The main aspects of the HIV and Mycobacterium tuberculosis coinfection in the adult patients attended by the main reference hospital for infectious diseases in the State of Ceará, Brazil, responsible for the notification of 89.3% of the cases registered in the state between 1986 and 1992 were investigated. METHODOLOGY: Data were collected from the case histories of patients of more than 15 years of age with a diagnosis of AIDS, attended in a state reference hospital in Northeastern Brazil. The analysis of the data obeys the criteria of the Ministry of Health for the definition of this disease. RESULTS: Tuberculosis had been present in 30.6% of the patients studied (151/493) and it was diagnosed by the first year after the AIDS diagnosis in 76.8% of the cases. The proportion of AIDS cases with tuberculosis is significantly greater (p=0,032) among men (94.7%) than among women (88.3%). An increased linear trend in the proportion of cases with tuberculosis was noticed in the AIDS cases according to the decrease in level of schooling (p<0,001). The direct baciloscopy of the sputum although considered a high priority exam, was made in only 72.9% of the patients, presenting positive results in 28.3% of these. The extrapulmonary form was detected in 23.9% of the cases and, among those, the miliary form in 25% and the meningitis in 16.7%. These results differ in a significant way (p<0,001 for all) from the cases with tuberculosis without HIV infection in adults registered in the state in 1992 (9.8% extrapulmonary, 7.2% miliary and 3.3% meningitis). In most cases, death occurred in the presence of tuberculosis (52.3%), and only 10.6% managed to recover from the tuberculosis. CONCLUSIONS: The premature development of tuberculosis in AIDS patients, the presence of a high percentage of extrapulmonary forms and the high lethality are indicators that the prevention and control measures of these two pathologies cannot be considered separately in this State.